Real-World Effectiveness of the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) mRNA Vaccines in Preventing Confirmed Infection in Patients on Chronic Hemodialysis. (9th February 2022) - Butt, Adeel A; Talisa, Victor B; Yan, Peng; Shaikh, Obaid S; Omer, Saad B; Mayr, Florian B
Abstract: Background: Persons on chronic hemodialysis have a significantly diminished humoral immune response to SARS-CoV-2 vaccines. Whether this translates to reduced vaccine effectiveness (VE) is unknown. Methods: We used the US Department of Veterans Affairs COVID-19 Shared Data Resource to identify all veterans who were tested for SARS-CoV-2 between 26 January and 31 August 2021. Using International Classification of Diseases, 10th edition, codes and attendance at a dialysis clinic/center, we identified those who were on chronic hemodialysis. We used a test-negative, case-control design using a doubly robust logistic regression model to determine the VE of the BNT-162b2 (Pfizer) or mRNA-1273 (Moderna) vaccines in preventing confirmed SARS-CoV-2 infection. Results: Among 847 199 veterans tested for SARS-CoV-2 between 26 January and 31 August 2021, there were 6076 veterans on chronic hemodialysis. Among those, we identified 1270 cases (580 fully vaccinated) and 2959 controls (2120 fully vaccinated). The overall VE >14 days after the second dose in preventing documented infection was 68.2% (95% CI: 62.6–72.9%). VE was 68.9% (95% CI: 61.9–74.7%) for Pfizer BNT-162b2 and 66.7% (95% CI: 58.9–73.0%) for Moderna mRNA-1273 vaccine. There was no difference in VE by age (<70 vs > 70 years), race, or sex. There were no events recorded in persons with a Charlson's comorbidity index score <2. Conclusions: VE of 2 doses of current mRNA vaccines in preventing SARS-CoV-2 infection in persons on chronic hemodialysis is lower than historic VE rates in the general population. Effects of additional doses in improving VE in this special population need further study. Abstract : Vaccine effectiveness for the currently available mRNA vaccines >14 days after the second dose was 68.2%. The effectiveness was 68.9% for the Pfizer BNT-162b2 and 66.7% for the Moderna mRNA-1273 vaccine.